Snakes in suits, revised edition : understanding and surviving the psychopaths in your office - Babiak, Paul (Tantor Media, 2019)
Revised and updated with the latest scientific research and updated case studies, the business classic that offers a revealing look at psychopaths in the workplace-how to spot their destructive behavior and stop them from creating chaos in the modern corporate organization.